BUMDES Develops Village Community Economy in Bulu-Bulu Village, Tonra District, Bone Regency - Ruslimin Ruslimin (Public Resource Innovation Management and Excellence, 2024)
This research aims to explain​ The role of BumDes in developing Community economy and supporting and inhibiting factors in the economic development of village communities in Bulu-Bulu Village , Tonra District, Bone Regency . The type of research used is qualitative research descriptive. It is said to be qualitative because the main data source in This research is in the form of an approach and actions of people who were observed and interviewed. Informants study is source person Which considered have knowledge Which widerelated problem Which currently researched, namely the Head of Bulu-Bulu Village , the Head of BUMDes , Secretary Treasurer BUMDes and the Community . The results of this study are that the role of BUMDes in developing the village community economy in Bulu-Bulu Village, Tonra District, Bone Regency is good but not yet significant for comprehensive economic development and the supporting factors faced by BUMDes. in improving the economic development of village communities in Bulu-Bulu Village, Tonra District, Bone Regency, namely the existence of strong support from the village government and the community as well as from the BUMDes management to maximize efforts to achieve the desired goals . Then the inhibiting factors faced by BUMDes In efforts to improve the economic development of rural communities , human resource compensation is still lacking.